Anesthetic Management of High-Risk Mitral Valve Replacement in a Young Adult with Posterior Leaflet Prolapse, Biventricular Dysfunction Risk, and Pulmonary Hypertension: A Case Report - Vera Muharrami; Robfadli Purnanda; Elwistrihady (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Mitral valve disease with concurrent pulmonary hypertension and biventricular dysfunction represents a complex surgical challenge requiring meticulous perioperative management. This case report presents the anesthetic approach to a 43-year-old male with severe mitral regurgitation secondary to posterior leaflet prolapse, Grade III diastolic dysfunction, and intermediate probability pulmonary hypertension undergoing elective mitral valve replacement. Case presentation: The patient presented with 6-month progressive dyspnea, chronic cough, bilateral lower-limb edema, and abdominal distension. Transthoracic echocardiography revealed severe mitral regurgitation with an effective regurgitant orifice area of 2.7 cm², bilateral atrial dilation, moderate tricuspid regurgitation, reduced tricuspid regurgitation jet velocity suggesting intermediate pulmonary hypertension probability, and preserved left ventricular ejection fraction of 68% with severely restrictive diastolic filling pattern. The patient underwent uncomplicated elective mitral valve replacement under general anesthesia with cardiopulmonary bypass. Intraoperative management emphasized hemodynamic stability through judicious fluid administration, careful anesthetic agent selection, and appropriate pulmonary vascular protection strategies. Cardiopulmonary bypass time was 125 minutes with an aortic cross-clamp time of 57 minutes. The postoperative course was uneventful with prompt extubation and discharge from intensive care on postoperative day three. Conclusion: This case illustrates the importance of comprehensive preoperative optimization, multimodal monitoring, and tailored intraoperative management in patients presenting with the complex intersection of severe organic mitral valve disease, pulmonary hypertension, and advanced diastolic dysfunction. The use of sevoflurane-based anesthesia, preservation of systemic vascular resistance, and lung-protective ventilation strategies contributed to favorable perioperative outcomes. This case highlights unique management considerations that may not be extensively detailed in standard anesthetic textbooks and demonstrates successful outcomes despite significant preoperative cardiac compromise.